Recent advances and future directions in banana molecular biology and breeding - Chunzhen Cheng; Shuofan Wu; Guiming Deng; Ou Sheng; Ganjun Yi; Qiaosong Yang (Molecular Horticulture)
Abstract Since publication of a draft genome of the doubled-haploid ‘Pahang’ banana (Musa acuminata, DH-Pahang), a new era for banana biology research has begun. With the release of genomic data from some important Musa species and subspecies and the continuous development of molecular biology techniques, significant progress has been made. Here, we summarize the achievements and advances in the banana molecular biology and breeding over the past decade covering origin and domestication, fruit biology, stress biology, and breeding aspects, and highlight their challenges and future perspectives. This review is intended to provide researchers with the latest information on the complex genetic background and evolutionary relationship of bananas, the biology of fruit ripening, and multi-omics-based stress biology research. We especially focus on recent advances in the molecular breeding of bananas, offering an informative research direction and providing valuable technical references for future research in the field.